Red seaweed pigments from a biotechnological perspective - Freitas, Marta V. (2022)
Algae taxa are notably diverse regarding pigment diversity and composition, red seaweeds (Rhodophyta) being a valuable source of phycobiliproteins (phycoerythrins, phycocyanin, and allophycocyanin), carotenes (carotenoids and xanthophylls), and chlorophyll a. These pigments have a considerable biotechnological potential, which has been translated into several registered patents and commercial applications. However, challenges remain regarding the optimization and subsequent scale-up of extraction and purification methodologies, especially when considering the quality and quantity needs, from an industrial and commercial point of view. This review aims to provide the state-of-the-art information on each of the aforementioned groups of pigments that can be found within Rhodophyta. An outline of the chemical biodiversity within pigment groups, current extraction and purification methodologies and challenges, and an overview of commercially available products and registered patents, will be provided. Thus, the current biotechnological applications of red seaweeds pigments will be highlighted, from a sustainable and economical perspective, as well as their integration in the Blue Economy.